Chromatic dialogues: colour and culture in Homer, Herodotus and the Hebrew Bible - Lyell, Ellena (2021)
Colour and culture are closely intertwined. Yet ancient texts – such as Homeric epic, Herodotus’ Histories and the Hebrew Bible – are still translated and interpreted with the assumption that the ancients perceived, classified and understood colour in the same way we do today. The conceptualisation of colour demonstrates a range of cultural nuances and offers insights into the thought processes of ancient society. Therefore, this study explores the nature of colour perception in the Hebrew Bible, using the categorisation and understanding of colour in Homeric epic and Herodotus’ Histories as a comparative perspective. Greek literary materials, such as the Iliad, Odyssey and Herodotus’ Histories, demonstrate that colours are categorised differently and used in a variety of ways that tie in with broader cultural themes. No biblical scholarship has scrutinized the intimate relationship between colour, culture and theology in a comprehensive way. This thesis begins by collating evidence for the classification of colours across the different literary corpora and exploring similarities and differences in patterns of usage. The chapter that follows takes one of the most evocative and versatile of these colours – purple – and closely examines its associations in both Greek and Hebrew literary contexts. This is then a springboard for a chapter on the materiality of colour in the Hebrew Bible. Ancient colours were fundamentally derived from and intertwined with material phenomena – bodies, objects and environment. As these materials were found throughout the ancient world, the next chapter analyses the provenances of these coloured materials, and the significance of these origins and associations for understanding the valency of colour in the Hebrew Bible. A final chapter applies these findings and the cultural connotations of colour categories to key biblical texts, and explores the extent to which colour in the Hebrew Bible is in constant dialogue with a broad range of social and cultural themes, and so acted as a theological marker and a literary device. This thesis demonstrates that the biblical authors associated themes of beauty, wealth and types of power with colour, and these themes manifested themselves vividly through ekphrasis, experience and the senses. Most significantly, colour is central to understanding the portrayal of the human and the divine, and by enriching our understanding of the texts provides new insight into the world in which these texts were produced.